Vascular effects dominate solid tumor response to treatment with combretastatin A-4-phosphate. - Lunt, S; Akerman, S; Hill, S; Fisher, M; Wright, V; Reyes-Aldasoro, C; Tozer, G; Kanthou, C (2011)
Vascular-targeted therapeutics are increasingly used in the clinic. However, less is known about the direct response of tumor cells to these agents. We have developed a combretastatin-A-4-phosphate (CA4P) resistant variant of SW1222 human colorectal carcinoma cells to examine the relative importance of vascular versus tumor cell targeting in the ultimate treatment response. SW1222(Res) cells were generated through exposure of wild-type cells (SW1222(WT) ) to increasing CA4P concentrations in vitro. Increased resistance was confirmed through analyses of cell viability, apoptosis and multidrug-resistance (MDR) protein expression. In vivo, comparative studies examined tumor cell necrosis, apoptosis, vessel morphology and functional vascular end-points following treatment with CA4P (single 100 mg/kg dose). Tumor response to repeated CA4P dosing (50 mg/kg/day, 5 days/week for 2 weeks) was examined through growth measurement, and ultimate tumor cell survival was studied by ex vivo clonogenic assay. In vitro, SW1222(Res) cells showed reduced CA4P sensitivity, enhanced MDR protein expression and a reduced apoptotic index. In vivo, CA4P induced significantly lower apoptotic cell death in SW1222(Res) versus SW1222(WT) tumors indicating maintenance of resistance characteristics. However, CA4P-induced tumor necrosis was equivalent in both lines. Similarly, rapid CA4P-mediated vessel disruption and blood flow shut-down were observed in both lines. Cell surviving fraction was comparable in the two tumor types following single dose CA4P and SW1222(Res) tumors were at least as sensitive as SW1222(WT) tumors to repeated dosing. Despite tumor cell resistance to CA4P, SW1222(Res) response in vivo was not impaired, strongly supporting the view that vascular damage dominates the therapeutic response to this agent.